Religious dissimulation and early modern drama : the limits of toleration - Schindler, Kilian (Cambridge University Press, 2023)
Examining how playwrights from Shakespeare to Marlowe represented religious dissimulation on stage, Kilian Schindler argues that debates about the legitimacy of dissembling one's faith were closely bound up with early modern conceptions of theatricality.